„Bulgarian” Yom-Kipour and Traditional Jewish Worldview (Forum Theologicum Sardicense, 2025)
Magdalena Kraycheva, „Bulgarian” Yom-Kipour and the Traditional Jewish Worldview. For Jews, understanding the Holocaust from a theological perspective is challenging for two main reasons: 1) The Holocaust is perceived as a form of ‘geninom’—a hell on Earth and a judgment upon the Jewish people. The meaning of this horrific genocide, which included the systematic massacre of Jews, including young children, is difficult to reconcile with the Jewish perception of themselves as a holy and chosen nation; 2) The lack of a concept of original sin, which is believed to be the primary cause of evil and suffering in the world, further complicates the Jewish understanding of the Shoah. Additionally, the rescue of the Bulgarian Jews raises another question: Why did the Jews in Bulgaria deserve their rescue more than their counterparts elsewhere in Europe?